Sectoral perspectives on the benefits of vocational education and training - (:unkn) unknown (Publications Office of the European Union, 2012)
"Job satisfaction is no luxury: it is an integral part of human resource policy and considerably affects productivity. But the relationship between job satisfaction and training varies significantly across sectors. This may be due to factors such as working practices in the sector, the technology used in production process, and social and cultural norms. The latest in Cedefop's series of studies on the benefits of vocational education and training discusses the variance of job satisfaction among sectors, and what role national or regional growth strategies can play in improving it. This paper shows that high value-added activities, which require firms to attract and retain a highly qualified workforce, tend to show higher job satisfaction. The case studies it includes show that public investment in training, catering to the specific needs of high value-added firms, can be very effective in inducing firms and stakeholders to work together: such cooperation acts as a boost to the entire sector. The evidence collected by Cedefop argues for integrating training in regional and sectoral growth strategies. Training institutions may then act as catalysts for the further development of industrial clusters. Smart growth in Europe would directly benefit from such integrated economic policies." (Hrsg., BIBB-Doku)
Keywords: Betriebliche Berufsausbildung; Betriebliche Weiterbildung; Arbeitszufriedenheit; Produktivität; Sektoransatz; Fallstudie; Europa